Individual Variation of Leptin, Nesfatin-1 and Irisin Levels During Aerobic Exercise Performed Morning and Night in Trained and Untrained Male Subjects - Algul, Sermin; Ozcelik, Oguz (Wiley-Blackwell, 2016)
[Abstract Not Available]